Retrospective analysis of technical success rate and procedure-related complications of 867 percutaneous CT-guided needle biopsies of lung lesions. Issue 12 (December 2017) - Mills, M.; Choi, J.; El-Haddad, G.; Sweeney, J.; Biebel, B.; Robinson, L.; Antonia, S.; Kumar, A.; Kis, B.
Abstract : Aim: To investigate the technical success rate and procedure-related complications of computed tomography (CT)-guided needle biopsy of lung lesions and to identify the factors that are correlated with the occurrence of procedure-related complications. Materials and methods: This was a single- institution retrospective study of 867 consecutive CT-guided needle biopsies of lung lesions performed on 772 patients in a tertiary cancer centre. The technical success rate and complications were correlated with patient, lung lesion, and procedure-related variables. Results: The technical success rate was 87.2% and the mortality rate was 0.12%. Of the 867 total biopsies 25.7% were associated with pneumothorax, and 6.5% required chest tube drainage. The haemothorax rate was 1.8%. There was positive correlation between the development of pneumothorax and smaller lesion diameter ( p< 0.001), longer transparenchymal distance ( p< 0.001), and prone position ( p =0.027). There was positive correlation between the need for chest tube placement and longer transparenchymal distance ( p =0.007) and smaller lesion diameter ( p =0.018). Lesions in the left lower lobe had the lowest rates of pneumothorax ( p =0.008) and chest tube drainage ( p =0.018). Patients whose pneumothoraces were diagnosed on the follow-up chest X-ray, but not on the immediate post-procedural CT scan had significantly higher requirement for chest tube drainage ( p =0.039). Conclusion: CT-guided lung biopsy has a high rate of technical success and a low rate of major complications. The present study has revealed several variables that can be used to identify high-risk procedures. A post-procedural chest X-ray within hours after the procedure is highly recommended to identify high-risk patients who require chest tube placement. Highlights: CT-guided percutaneous lung biopsy has 87.2% technical success rate. 25.7% were associated with pneumothorax, and 6.5% required chest tube placement. Smaller lesion and longer biopsy distance were associated with chest tube placement. A post-procedural chest x-ray within hours after lung biopsy is highly recommended.